(untitled) (World Bulletin of Management and Law, 2022)
Russian classical poetry forms in a person love for the native nature, respect for the native home. And it was Sergei Yesenin who dedicated his work to nature, the Motherland and love. I wanted to learn more about his work and life, about how he wrote poetry, what difficulties he experienced in his life. Contemporaries considered Sergei Alexandrovich a worthy successor to Pushkin’s glory, but unlike A.S. Pushkin, Yesenin had a short life and a mysterious death